The Marketplace : an ethnographic case study of Sungei Road market. - Nurul Afiah Abdul Rashid. (2010)
The study for markets, as part of the informal economy, has traditionally been understood from a neoclassical economic approach. However, this case-study of a particular type of market, Sungei Road market (SR) in Singapore attempts to provide a deeper and complex understanding of market/marketplace activity. It that takes into account not just the economic, but social and political processes too. A detailed ethnographic observation of SR is presented in this paper and market activity is understood from an economic sociology perspective. This paper explores market mechanisms (such as pricing and bargaining), diverse interactions from three webs of exchanges: 1) between vendors 2) between vendors and customers, and 3) between vendors and relevant authorities. In addition, an exploration of ‘survival strategies’ is presented. Thus, I argue that street vending can be seen beyond just “the marketplace” and these vendors situate themselves within the marketplace, in terms of their interactions and resources.